First occurrence in mangroves of South America of the exotic species Sonneratia apetala Buch.-Ham. from the Indo-Malayan region - Eysink, Geraldo Guilherme José [UNESP]; Hatamura, Edmar; Schaffer-Novelli, Yara (FapUNIFESP (SciELO), 2023)
This is the 1st record of the Sonneratia apetala Buch.-Ham., in the mangroves of South America – Cubatão-Baixada Santista, State of São Paulo, Brazil. The record was made in an area located 2 km apart from the port of Santos. Its arrival was probably made through the ballast water. S. apetala as well an exotic it is also an aggressive mangrove species. All 85 individuals identified were georeferenced. In May 2023 they were flowering and in August they already had ripe fruits/propagules. The presence of exotic species in mangroves is worrying, they can cause profound ecological and economic impacts and negatively influence the restoration of native ecosystems. The presence of S. apetala in the mangroves of Cubatão region could bring about a radical change in the biological structure of the mangrove ecosystem, in addition to being a new point of dispersal to others areas.
Primeiro registro nos manguezais da América do Sul da espécie exótica Sonneratia apetala Buch.-Ham da região Indo-Malaia
Keywords: Ballast water; biological invasions; invasive species; mangrove; Sonneratia apetala; South America